Climate change – analysis of indicators - Muszyński, Robert; Kocur-Bera, Katarzyna (International Conference “Environmental Engineering”, 2020)
Progressing climate change poses a major threat to the Earth. According to a UN report, reducing global warming to below 1.5 °C offers hope for maintaining the current quality of human lives and for protecting the environment. The report also points out that there is a prescription for curbing the catastrophic effects of climate change. In order to achieve the aim of stopping the increase in temperature, both adequate knowledge of the hazard and measures based on proven technologies are required. The first step that will enable the commencement of activities is to identify the hazard characteristics and their effect on the environment. In this regard, various types of indicators that cover the local, regional and global scale in various aspects, both environmental and anthropogenic, are very helpful. The main purpose of the analysis is to examine indicators/indices that synthetically express/define various aspects which reflect climate change. The study applied the method of research of the available literature. The analysis showed that the economies of countries use indicators that describe the different scale of impact and a different objective and subjective range. This is mainly determined by the needs and accessibility of data.
Keywords: land management; globe protection; indicators of climate change